The Role of Global Commodity Prices in the Dynamics of the Business Cycle in Indonesia - Deswita Herlina; Doni Satria (Jurnal Ekonomi Pembangunan, 2025)
This study examines the dynamic impact of global export commodity price fluctuations on the Indonesian economy, a representative small open economy with a significant reliance on primary resources. Using a Structural Vector Autoregression (SVAR) framework and quarterly data spanning from 1993 to 2019, the research analyzes the transmission of price shocks to the terms of trade, trade balance, and domestic business cycle variables, including per capita output, consumption, and investment. The empirical findings reveal that a positive shock to export commodity prices initially leads to a deterioration in the trade balance—consistent with the J-curve effect—due to the inelastic nature of imported industrial inputs and energy. However, the medium-term analysis identifies a significant "wealth effect," where increased export revenues stimulate domestic investment and consumption. Forecast error variance decomposition results further indicate that commodity price shocks are a dominant driver of trade balance volatility, accounting for nearly 48% of its variance over a 12-quarter horizon. At the same time, their impact on the broader business cycle remains persistent but modest. Robustness checks using a VARX model confirm these results, asserting the exogeneity of commodity prices. Policy implications suggest that Indonesia should utilize counter-cyclical fiscal buffers and maintain a flexible exchange rate to mitigate external volatility and prevent "Dutch disease" symptoms.